2015
DOI: 10.1007/s11355-015-0273-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in epiphyte diversity in declining forests: implications for conservation and restoration

Abstract: Biodiversity degradation is a serious global problem, and conservation or restoration has been conducted in various ecosystems. The objective of this study was to examine effective conservation measures and restoration goals for epiphytes on the basis of changes in epiphyte flora during the past 30 years on Mt. Odaigahara, Japan. Comparison of epiphyte diversity between 1983 and 2008 indicated that species richness and cover in plots surveyed in 1983 had declined significantly by 2008. The results of nonmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Two indicators of successful restoration of temperate rainforests are regeneration of long-lived, shade-tolerant trees (Suganuma andDurigan 2015, Johnson andHandel 2016) and colonization by epiphytes (Oishi andDoei 2015, Reid et al 2016). Spontaneous dispersal and recruitment of these indigenous, late successional plants into a forest undergoing restoration is an indication that conditions have become suitable for natural forest dynamics to occur without additional management actions (Robinson and Handel 1993, Boudreault et al 2000, Shoo et al 2015, Bertacchi et al 2016.…”
mentioning
confidence: 99%
“…Two indicators of successful restoration of temperate rainforests are regeneration of long-lived, shade-tolerant trees (Suganuma andDurigan 2015, Johnson andHandel 2016) and colonization by epiphytes (Oishi andDoei 2015, Reid et al 2016). Spontaneous dispersal and recruitment of these indigenous, late successional plants into a forest undergoing restoration is an indication that conditions have become suitable for natural forest dynamics to occur without additional management actions (Robinson and Handel 1993, Boudreault et al 2000, Shoo et al 2015, Bertacchi et al 2016.…”
mentioning
confidence: 99%
“…The combined impacts of multiple stresses on plant physiology can exponentially impact species biology [ 21 ]. The loss of tropical and temperate primary forests is linked to the disappearance of moist-sensitive fern epiphytes [ 25 , 40 ]. This could also happen in our case, as we have observed that well-structured non-fragmented forests seem to smooth the reduction of maximum germination or the delay in the onset of germination, due to increasing temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding germination, epiphytes are affected by increasing temperatures due to global warming [ 17 , 19 , 21 ]. Forest structure related to fragmentation is also linked to epiphytic abundance as well-structured complex forests generate more buffered micro-conditions which maintain suitability for the epiphytic habit [ 20 , 22 , 24 , 25 ]. The loss of forest structure due to fragmentation and clearness of the canopy affects, at least, epiphytic community composition by reducing individuals of intolerant species and promoting new suitable opportunities to tolerant ones [ 19 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid changes in forest landscapes due to urbanization, agriculture, road construction, and especially deforestation have caused forest loss and fragmentation, threatening forest biodiversity worldwide ( Elliott & Swank, 1994 ; Imai et al, 2014 ; Jung et al, 2014 ). Urgent intervention for conserving biodiversity and forest remnants is thus necessary ( Jactel & Brockerhoff, 2007 ; Nyafwono et al, 2014 ; Oishi & Doei, 2015 ).…”
Section: Introductionmentioning
confidence: 99%